Israel attacks an ‘aid’ flotilla bound for Gaza: a dark day for international law - Bosch, S. (Faculty of Law, University of the Free State, 2010)
This paper examines the Israeli raid on six aid vessels bound for Gaza on 31 May 2010, in light of customary International Humanitarian Law (IHL). In exploring the international law implications of these events, the concepts of a legal maritime blockade and the use of force to impose such a blockade are unpacked. The article considers whether the use of force by the civilians on board the vessels amounted to ‘direct participation in hostilities’, and whether either side might have a legitimate claim to have acted in self-defence. Lastly, the obligations placed upon belligerents when they detain civilians are examined, in light of the fundamental guarantees of humane treatment enshrined in IHL.
Keywords: Gaza; International humanitarian law; Civilians; Israel